Extract of Aronia melanocarpa-modified hemostasis: in vitro studies - Sikora, Joanna (Springer Berlin Heidelberg, 2014)
PURPOSE: Aronia melanocarpa has an extremely high content of procyanidins and anthocyanins. The multidirectional benefits of consumption of these berries are widely reported. Although numerous studies confirmed the influence of polyphenols on various stages of hemostasis, the exact mechanism of this phenomenon is not understood. The aim of our study was to evaluate the in vitro effect of A. melanocarpa extract on various parameters of hemostasis. METHODS: Adenosine 5′-diphosphate (ADP)-induced aggregation was measured with turbidimetric method. Spontaneous and ADP-activated platelet adhesion were investigated using a colorimetric method. The global assay of coagulation and fibrinolysis was performed with the use of optical clotting and lysis (CL) test. Thrombin (0.5 IU/mL) and tissue plasminogen activator (60 ng/mL) were used to obtain a CL curve. The activity of thrombin and plasmin was determined by means of chromogenic substrate (S-2238, S-2251) RESULTS: The aronia extract contributed to the reduction in spontaneous and ADP-activated platelet adhesion. A significant increase in overall potential of CL as well as significant changes in key parameters of these processes (T (t)—thrombin time, F (vo)—initial plasma clotting velocity, and L (max)—maximum lysis) was reported. Chokeberry extract significantly inhibited the amidolytic activity of thrombin and plasmin. CONCLUSION: Our in vitro findings indicate a complex mechanism of influence of chokeberry polyphenols on platelet activity and the overall potential of CL. We confirmed that chokeberry inhibits the amidolytic activity of thrombin. It was demonstrated for the first time that chokeberry polyphenols inhibit the amidolytic activity of another serine protease, i.e., plasmin, which is the main fibrinolytic enzyme. Furthermore, our research points out a significant contribution of other plasma components and fibrinogen in the modulation of hemostasis by polyphenols.